2014
DOI: 10.3346/jkms.2014.29.4.581
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Surgical Ligation for Patent Ductus Arteriosus Is Associated with Neonatal Morbidity in Extremely Preterm Infants Born at 23-25 Weeks of Gestation

Abstract: The purpose of this study was to evaluate prognostic factors associated with surgical ligation for patent ductus arteriosus (PDA) in extremely preterm infants born at the limits of viability. Ninety infants who were born at 23-25 weeks of gestation and who received surgical ligation were included and their cases were retrospectively reviewed. Infants were classified into two different groups: survivors with no major morbidity (N), and non-survivors or survivors with any major morbidity (M). Clinical characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…Sung et al. showed that delayed surgical ligation of the PDA beyond two weeks was associated with reduced neonatal morbidity. The increasing controversy regarding early treatment of PDA has led to a trend towards an expectant management and delaying medical treatment, rather than treating when the infant exhibits subtle signs of a PDA, a practice that is growing amongst neonatologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sung et al. showed that delayed surgical ligation of the PDA beyond two weeks was associated with reduced neonatal morbidity. The increasing controversy regarding early treatment of PDA has led to a trend towards an expectant management and delaying medical treatment, rather than treating when the infant exhibits subtle signs of a PDA, a practice that is growing amongst neonatologists.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous ductal closure in preterm infants has been associated with the administration of antenatal steroids, being small for gestational age (GA) and lack of hyaline membrane disease . Despite several randomised controlled trials, the timing and method of treatment remains unclear and clinical practice for treating PDA varies widely . Randomised trials comparing early PDA treatment with placebo or delayed treatment showed no difference in long‐term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, ventilated preterm infants were randomized at the end of the first week to either surgical PDA ligation or “no treatment”. Despite the fact that performing a surgical ligation increases the risks of pulmonary morbidity (2433), the authors found that infants in the surgical treatment arm had a lower incidence of pulmonary morbidity than infants with a persistent PDA in the “no treatment” arm of the study.…”
mentioning
confidence: 94%
“…With this type of respiratory management there is no evidence that early surgical PDA closure prevents the evolution of BPD (24, 34, 3739). In fact, many of the morbidities associated with ligation (post-ligation hypotension (31), vocal cord paralysis (40), bronchopulmonary dysplasia (24)) and abnormal neurocognitive development (32)) appear to be reduced when ligation is delayed for at least several weeks (33). At this point in time, avoiding surgical ligation or delaying it until late in the neonatal course appears to be preferable to ligating the PDA within the first 2–3 weeks.…”
mentioning
confidence: 99%
“…Many studies on surgical ligation have reported adverse outcomes such as increased BPD in association with surgical ligation (32). The timing of PDA ligation is also important for determining the neonatal outcomes (33). Thus, targeted treatment is important to reduce such adverse effects, and knowing early markers of hsPDA that indicate the need for treatment will be beneficial.…”
Section: Discussionmentioning
confidence: 99%